An evaluation of the socio-economic costs and benefits of the invasive Rubus (Blackberry/Bramble) genus at selected sites in South Africa - Mason, Brett Anthony (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
Rubus L. (brambles, blackberries, raspberries, or dewberries) are a globally recognised genus due to the edible fruit and negative impacts they can have as invasive species. There are at least 23 species of Rubus subgenus Rubus in South Africa. These include native, alien, naturalised alien, and invasive alien species. The invasive Rubus species are becoming an increasing problem in South Africa with experts in invasion biology urging caution regarding the genus (Henderson, 2011). The taxonomy of indigenous, alien and alien invasive species of Rubus are poorly understood and therefore efforts to understand the genus, the impacts and solutions to those impacts have been very limited (Stirton, 1981; Henderson, 2011; Sochor et al., 2018a). There has also been little research conducted on the economic or ecological impacts on the species or genus of species in South Africa (du Plessis et al., 1984; Botha, 2005), and yet species in the genus have been earmarked for prioritization by invasive species legislation. The potential value of certain species as well as the cost associated with their impacts could potentially create a complex conflict of interest scenario which has not been investigated. This study is an effort to inform future policy decisions regarding this suite of species by investigating the economic impacts of the invasive Rubus species. A method was developed unique to the study that incorporated research tools from environmental economics and geography to identify the nature of interactions between economic agents, experts, and alien and invasive Rubus species in South Africa. Two questionnaires were developed to generate economic data and ground proofing was used to develop geographic data. One questionnaire was directed specifically at researchers and academics that attended the 46th National Symposium on Biological Invasions that took place between 15"“17 May 2019, at Waterval Country Lodge, Tulbagh and the other an economic agent questionnaire for economic agents that met strict and selective criteria relating to the impact of the six invasive Rubus species on their economic activity. Both questionnaires were designed with a mixed methods approach in mind. The ground proofing was aimed at understanding the composition and distribution of Rubus species at the selected sites: Cathcart and Hogsback (The Eastern Cape Province), Clarens (Free State Province), and Underberg (KwaZulu-Natal Province). The study established that all economic impacts of invasive Rubus species at selected sites are externalities. Invasive Rubus species in South Africa can be attributed as (i) harbouring vermin, (ii) impeding human and animal livestock, (iii) reducing crop yields, (iv) encroaching on grazing land, (v) presenting fire hazards, and (vi) negatively impacting fire regimes. These species also (i) provide berries that are retailed on a commercial level, or have been, (ii) that are utilized for personal consumption, (iii) provide an ingredient for alcohol brewing processes, and (iv) could potentially facilitate forest regeneration. The invasive species are infrequently browsed by certain livestock and far as we could ascertain do not provide ingredients for anti-inflammatory drugs or modern cosmetics in South Africa, as they do in other regions of the globe. The costs associated with the invasive species can be presented dichotomously; the estimated private cost-benefit ratio, for costs and benefits incurred or enjoyed by 18 private economic agents, stands at 0.33:1. A private-public benefit-cost ratio, that incorporates both private and public costs and benefits, stands at 13,5:1. The private-public benefit-cost includes public expenditure, or government control measures, directed at invasive Rubus and shifts the benefit-cost ratio so that costs now markedly dominate the estimated benefits. The benefits per hectare uncovered in this study stand at R13.14/ha. The private costs stand at R4.32/ha and a holistic cost, including both private and public expenditure, stands at R177,43/ha. The monetary values, when expressed per hectare, are misleading. This is due to a large standard deviation in the spread of benefits received. The benefits are enjoyed by a small number of the already small sample of respondents. The costs and benefits are not uniformly distributed across regions assessed. All benefits in this study accrue to economic agents in the Free State Province, whilst most of the costs accrued to economic agents in KwaZulu-Natal Province. The benefits appear to be primarily derived from an alien species, Rubus sect. Arguti. Management of the 6 species of invasive Rubus could be optimised by the prioritisation of those regions that incur the highest cost and derive the lowest benefit, in this case KwaZulu-Natal Province. Likewise, those regions with the highest benefits and lowest costs, the Free State Province, could provide sites for increased use and beneficiation of berries from invasive species. Management of individual species may prove difficult, given the similar morphologies, and thus, (i) either specialised training for those engaged in control must be instituted, (ii) all species of alien Rubus should be earmarked for management, or (iii) highly specific biocontrol agents for the most problematic species must be found.
Keywords: Rubus -- South Africa Cost effectiveness; Invasive plants -- South Africa Cost effectiveness; Rubus Economic aspects -- South Africa; Ecology Economic aspects -- South Africa; Rubus Ecology -- South Africa; Environmental economics -- South Africa